Teacher as Counselor: A Qualitative Descriptive Study of the Counseling-Learning Method in Arabic Language Learning - nur rahmawati; Asnawi; AM. Maqdum Biahmada (Universitas Islam Tribakti Lirboyo, Kediri, 2026)
Speaking skills (maharah kalam) in Arabic language learning are frequently impeded by language anxiety rooted in conventional approaches that rely on rote memorization and aggressive grammatical correction. This study aims to (1) describe the psychological dynamics of the five stages of the Counseling-Learning Method (CLM) in reducing language anxiety, (2) analyze the manifestation of the lecturer's role transformation as a counselor and students as clients, and (3) explain the impact of such psychological intervention on students' communicative autonomy in producing Arabic. This qualitative study employing a descriptiveanalytical method involved 20 fourth-semester Arabic Language Education students and one lecturer at Institut Attanwir Bojonegoro, selected through purposive sampling. Data were collected through participatory observation and indepth interviews, then analyzed via data reduction, data display, and conclusion drawing, with technique triangulation applied to ensure validity. The findings reveal that: first, language anxiety was gradually reduced through Curran's five psychological stages — from absolute dependence to full independence — by delaying aggressive correction in the initial phase; second, an emotionally safe classroom climate was established through the lecturer's transformation from an authoritative figure into a facilitator, psychological incubator, and non-judgmental validator; and third, the decline in the affective filter had a significant impact on eliminating students' dependence on memorized scripts, enabling them to construct sentences, engage in discussion, and achieve speaking fluency autonomously, spontaneously, and meaningfully. The novelty of this study lies in its in-depth qualitative exploration of the psychological dynamics between lecturer and students in a pesantren-based higher education context, a dimension that remains underexplored in existing literature